2015
DOI: 10.1038/srep14267
|View full text |Cite
|
Sign up to set email alerts
|

A size-dependent structural evolution of ZnS nanoparticles

Abstract: Recently, ZnS quantum dots have attracted a lot of attention since they can be a suitable alternative for cadmium-based quantum dots, which are known to be highly carcinogenic for living systems. However, the structural stability of nanocrystalline ZnS seems to be a challenging issue since ZnS nanoparticles have the potential to undergo uncontrolled structural change at room temperature. Using the molecular dynamics technique, we have studied the structural evolution of 1 to 5 nm freestanding ZnS nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 42 publications
4
34
0
Order By: Relevance
“…The first peak distance becomes larger as particle size increases. A similar observation is also found in nanometer-sized crystalline ZnS particles 42 , 43 . To dig out details of local atomic structure in particles, the core-and-shell model in the inset of Fig.…”
Section: Resultssupporting
confidence: 83%
“…The first peak distance becomes larger as particle size increases. A similar observation is also found in nanometer-sized crystalline ZnS particles 42 , 43 . To dig out details of local atomic structure in particles, the core-and-shell model in the inset of Fig.…”
Section: Resultssupporting
confidence: 83%
“…It has been shown that nanoparticles can go through massive surface relaxations, sometimes, can even change their crystal structures. 27,28 Moreover, these methods cannot provide information about the effect of the line tension when a possible size effect at the nanoscale is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…This is evidence of reduced crystallinity in nanoparticles [15]. Also, since the ionic radius of Mo +6 (0.065 nm) is smaller than the ionic radius of Zn 2+ (0.074 nm), it may cause a stress in the lattice [16].…”
Section: Resultsmentioning
confidence: 97%